Effects of heat treatment on the microstructures and electrochemical behavior of stainless steel - Haslan, Nur Hasmisha (2013)
The objective of this project is to investigate the effects of heat treatment parameters on corrosion resistance and phase transformation in relation to the microstructures and electrochemical behaviors of austenitic 304 and martensitic 420 stainlesssteel. In this project, there are several heat treatment parameters under investigation namely annealing at temperature 900 °C and 1000°C and normalizing with difference soaking times. Other heat treatment process carried out on martensitic stainless steel only is quench and temper. Corrosion test was conducted on non-treated and heat treated samples according to British Standard (BS ISO 17475:2005) for electrochemical test (Tafel test). Hardness test was also carried out on the non-treated and heat treated samples using Vickers hardness test. Microstructure analysis was performed on the samples using characterization equipment such as Glow Discharge Spectroscope (GDS), Optical Microscope (OM), Scanning Electron Microscope (SEM), Energy Dispersive X-ray (EDX) and X-ray Diffraction (XRD). The results shows that heat treatment affect the microstructures and electrochemical behaviors of stainless steel. It was also found that higher temperature gives lower hardness. From the corrosion test results, it can be concluded that higher austenization temperatures and higher normalizing soaking times improved the corrosion resistance of stainless steel due to increase in grain size and less in formation of carbides. These carbides will contribute to the corrosion whereby it provides sites for anodic and cathodic reaction to occur between the carbide and the matrix phases